Analisis Faktor yang Mempengaruhi Keberadaan Bakteri Escherichia Coli Pada Sumur Gali - Hardianti, Iin; Yustati, Eva; Heriyanto, Eko (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Dug wells are the main source of clean water supply for residents living in rural and urban areas in Indonesia. Dug well water is very easily contaminated by bacteria originating from wastewater or human waste. The aim of the research is to find out the factors that influence the presence of ecoli bacteria, using a cross sectional research design. The population in the study was 116 dug wells with the number of samples needed being 89. Samples using a random sampling technique. The results of the univariate analysis showed that there were 89 respondents. 38 (42.7%) respondents were there, 51 (57.3%) were not there. 45 (50.6%) respondents whose Sepitctank Distance did not meet the requirements met the requirements as many as 44 (49.4%). 40 (44.9%) respondents whose physical condition of the dug well did not meet the requirements were that the physical condition of the dug well met the requirements, as many as 54 (60.7%). Bivariate analysis Chi Square statistical test of septic tank distance, waste accumulation distance and physical condition of dug wells obtained a p value of 0.000. Conclusion. There is a significant relationship between the distance between septic tanks and the physical condition of dug wells with the presence of E coli bacteria in dug wells in Lubuk Empelas Village, Muaraenim District in 2024